Indications and Complications of Orthopedic Hardware Removal in an Indonesian Tertiary Hospital: A Descriptive Study - Shadrina Affifa Azzahra; Raden Andri Primadhi; Titing Nurhayati; Muhammad Naseh Sajadi; Achadiyani Achadiyani (Faculty of Medicine Universitas Padjadjaran, 2022)
Objective: To acquire clinical data regarding indications of implant removal and complications in orthopedic metal implant removal. Methods: This was a cross-sectional observational descriptive study using patient medical records. The inclusion criterion was all patients who underwent orthopedic metal implant removal during 2018-2020 while the exclusion criterion was unintentional implant removal due to subsequent injury or loosening. Data regarding anatomic regions, indications, and complications were collected and presented in tables.Results: In 112 patients participated in this study consisting of 75 (67%) men and 37 (33%) women, the implants were mainly located in thigh, lower leg, and ankle (53% combined). The most common indication for metal implant removal was conversion (31%), followed by infection (25%) and patient's request (20%). The only complication observed in orthopedic metal implant removal in this study was disturbed wound healing in a small percentage of the patients (16%). Most patients (84%) did not experience any complication due to metal implant removal.Conclusions: Indications for metal implant removal may vary, with or without symptoms. Disturbed wound healing is a complication observed in metal implant removal. Despite the advantages of removal, further analysis and guidelines are needed to avoid unnecessary hardware removal considering the risk of complications.